Thailand : The Road to Sustained Growth - Offerdal, Erik.; Dicks-Mireaux, Louis; Kochhar, Kalpana; Zhou, Jianping (Washington, D.C. : International Monetary Fund, 1996)
Since the mid-1960s, Thailand's growth performance has been exceptional. Although hard hit by the external shocks fo the late 1970s and the early 1980s that proved severely destabilizing to many developing countries, Thailand showed remarkable reslience: price stability was quickly restored, and the Thai economy emerged from this period with strong recovery in growth and investment, in an environment of overall macroeconomic stability. This study examines the evolution of investment and growth and Thailand's macroeconomic and structural policies, with a view to understanding the main factors that have led to this impressive economic performance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet